The Effect of Polarized Polychromatic Noncoherent Light (Bioptron) Therapy on Patients with Carpal Tunnel Syndrome - Raeissadat, Seyed Ahmad; Rayegani, Seyed Mansoor; Rezaei, Sajad; Sedighipour, Leyla; Bahrami, Mohammad Hasan; Eliaspour, Dariush; Karimzadeh, Afshin (Journal of Lasers in Medical Sciences, 2013)
Introduction: To study the effects of Polarized Polychromatic Noncoherent Light (Bioptron) therapy on patients with carpal tunnel syndrome (CTS). Methods: This study was designed as a randomized clinical trial. Forty four patients with mild or moderate CTS (confirmed by clinical and electrodiagnostic studies) were assigned randomly into two groups (intervention and control goups). At the beginning of the study, both groups received wrist splinting for 8 weeks. Bioptron light was applied for the intervention group (eight sessions, for 3/weeks). Bioptron was applied perpendicularly to the wrist from a 10 centimeters distance. Pain severity and electrodiagnostic measurements were compared from before to 8 weeks after initiating each treatment. Results: Eight weeks after starting the treatments, the mean of pain severity based on Visual Analogue Scale (VAS) scores decreased significantly in both groups. Median Sensory Nerve Action Potential (SNAP) latency decreased significantly in both groups. However, other electrophysiological findings (median Compound Motor Action Potential (CMAP) latency and amplitude, also SNAP amplitude) did not change after the therapy in both groups. There was no meaningful difference between two groups regarding the changes in the pain severity. Conclusion: Bioptron with the above mentioned parameters led to therapeutic effects equal to splinting alone in patients with carpal tunnel syndrome. However, applying Bioptron with different therapeutic protocols and light parameters other than used in this study, perhaps longer duration of therapy and long term assessment may reveal different results favoring Bioptron therapy.